Power Efficiency of Systems Applied for Heating Building and Structure External Walls with Ventilated Air Spaces - I. F. Fialko; A. S. Statsenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers power-efficient systems applied for heating building and structure external walls with ventilated air spaces and prescribes directions and problems pertaining to power-efficiency improvement of such systems.